Once-daily Doravirine in Human Immunodeficiency Virus Type 1–Infected, Antiretroviral-naive Adults: An Integrated Efficacy Analysis. (23rd May 2019) - Orkin, Chloe; Molina, Jean-Michel; Lombaard, Johan; DeJesus, Edwin; Rodgers, Anthony; Kumar, Sushma; Martin, Elizabeth; Hanna, George; Hwang, Carey
Abstract: Background: Doravirine (DOR) demonstrated noninferior efficacy to darunavir plus ritonavir (DRV+r) and efavirenz (EFV) in 2 ongoing phase 3 trials: DRIVE-FORWARD (NCT02275780) and DRIVE-AHEAD (NCT02403674). Methods: This prespecified analysis pooled efficacy data through the first 48 weeks of DRIVE-FORWARD and DRIVE-AHEAD from the DOR groups (DOR/lamivudine [3TC]/tenofovir disoproxil fumarate [TDF] or DOR [100 mg daily] with emtricitabine [FTC]/TDF or abacavir [ABC]/3TC [n = 747]) compared with DRV+r (800/100 mg daily) with FTC/TDF or ABC/3TC (n = 383) or EFV/FTC/TDF (600/200/300 mg daily; n = 364). Efficacy assessments included the proportion of participants with human immunodeficiency virus type 1 (HIV-1) RNA <50 copies/mL and change in CD4+ T-cell count. Results: At week 48, DOR demonstrated noninferior efficacy to DRV+r and EFV, with 84.1% of DOR-treated participants achieving HIV-1 RNA <50 copies/mL compared with 79.9% of the DRV+r and 80.8% of the EFV groups. Results were similar across demographic/prognostic subpopulations, including baseline plasma HIV-1 RNA, gender, race, and HIV-1 subtype. Mean increases from baseline in CD4+ T-cell count through 48 weeks were 195.5 cells/mm 3 for DOR, 185.6 cells/mm 3 for DRV+r, and 188.4 cells/mm 3 for EFV/FTC/TDF. Conclusions: DOR, as a single entity (in combination with other antiretroviral agents) and as a fixed-dose combination (DOR/3TC/TDF), demonstrated noninferior efficacy to DRV+r and EFV as assessed by the proportion of HIV-1-infected, treatment-naive adults with HIV-1 RNA <50 copies/mL. Clinical Trials Registration: NCT02275780 and NCT02403674. Abstract : At week 48, doravirine demonstrated noninferior efficacy to darunavir plus ritonavir and efavirenz, with 84.1% of doravirine-treated participants achieving human immunodeficiency virus type 1 RNA <50 copies/mL compared with 79.9% of the darunavir plus ritonavir and 80.8% of the efavirenz groups.